2017
DOI: 10.1038/s41598-017-08181-w
|View full text |Cite
|
Sign up to set email alerts
|

Wheat TaPUB1 modulates plant drought stress resistance by improving antioxidant capability

Abstract: E3 ligases play significant roles in plant stress tolerance by targeting specific substrate proteins for post-translational modification. In a previous study, we cloned TaPUB1 from Triticum aestivum L., which encodes a U-box E3 ligase. Real-time polymerase chain reaction revealed that the gene was up-regulated under drought stress. To investigate the function of TaPUB1 in the response of plants to drought, we generated transgenic Nicotiana benthamiana (N. benthamiana) plants constitutively expressing TaPUB1 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 54 publications
(60 reference statements)
3
37
0
Order By: Relevance
“…Our results indicate that AtPUB46 is a positive regulator of the response to drought as OE plants display improved tolerance and knock-down mutants are hypersensitive [11]. This is similar to OE of rice OsPUB15 [28], or wheat TaPUB1 [29] in transgenic rice or Nicotiana benthamiana, respectively, which also increased drought tolerance. This is in marked contrast to the majority of PUB genes that have been studied where overexpression resulted in hypersensitivity to drought [30][31][32][33][34][35].…”
Section: 1supporting
confidence: 64%
“…Our results indicate that AtPUB46 is a positive regulator of the response to drought as OE plants display improved tolerance and knock-down mutants are hypersensitive [11]. This is similar to OE of rice OsPUB15 [28], or wheat TaPUB1 [29] in transgenic rice or Nicotiana benthamiana, respectively, which also increased drought tolerance. This is in marked contrast to the majority of PUB genes that have been studied where overexpression resulted in hypersensitivity to drought [30][31][32][33][34][35].…”
Section: 1supporting
confidence: 64%
“…The CAT, SOD, ascorbate peroxidase (APX), POD and contents of soluble sugar and proline were detected according to previous reports (Zhang et al 2017a).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, a wheat gene TaPUB1 was identified. By heterologous overexpression of TaPUB1 in the dicotyledonous model plant Nicotiana benthamiana , we found this gene improved plant salt and drought stress tolerance (Zhang et al 2017a, 2017b). However, it remained unclear whether TaPUB1 could regulate the tolerance of wheat under salt stress.…”
Section: Introductionmentioning
confidence: 95%
“…To cope with this, plants have evolved enzymatic mechanisms for ROS scavenging . Hence, following physio‐morphological trait examinations, other indicators, such as redox status, cell membrane stability indexes, and ROS scavenging enzyme activities are normally measured to estimate the stress status …”
Section: Introductionmentioning
confidence: 99%